(untitled) (KULT_online, 2019)
In Backlash: What Happens When We Talk Honestly about Racism in America, George Yancy, scholar of the philosophy of race, shares the racist backlash he encountered as a reaction to his open letter “Dear White America.” Besides reproducing the original letter – a decisive call for an honest contestation of white racism in the US – the volume courageously engages with the various manifestations of hate speech it elicited. Most importantly, Yancy further conceptualizes the possibility of forging a coherent antiracist white subject position which he finds exemplified in some of the positive responses to his letter.